Pengaruh Modul Berbasis Problem Solving untuk Memberdayakan Logical Thinking pada Pelajaran Pewarisan Sifat - Baety Nur Hanifah; Sutarno Sutarno; Sri Widoretno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Problem solving is a skill have a role in logical thinking. Logical thinking can be obtained by applying problem solving in learning by using media such as module. The module used in the study is the result of development according to indicators compiled based on aspects of problem solving and logical thinking. The purpose of thestudy is to show the effect of problem solving-based module to empower logical thinking on the Inheritance of Traits lessons. The research method is quasi-experiment with pretest post-test non-equivalent control group design. The research participants are high school students in grade XII. There are control classes andexperimental classes. The results of the study showed that: 1) The score post-test of logical thinking in the experimental class is significantly different from the control class (0.00<0.05); 2) The logical thinking score in the experimental class is higher than in the control class; 3) The problem-solving based module has an 18%effect on logical thinking. Therefore, the use of problem-solving based module has positive effect on logical thinking skills in the Inheritance of Traits lessons.